Beneficial Effects of Quercetin on Microcystin-LR Induced Tight Junction Defects - Zhou, Yuan; Xue, Mei; Jiang, Yunfei; Zhang, Miaomiao; Wang, Changming; Wang, Xuyang; Yu, Guang; Tang, Zongxiang (Frontiers in Pharmacology, 2021)
Quercetin has numerous functions including antioxidant and anti-inflammatory effects. The beneficial effect of quercetin against microcystin-LR (MC-LR)-induced testicular tight junction defects in vitro and in vivo were investigated. Significant reductions in transepithelial electrical resistance, occludin, and zonula occludens-1(ZO-1) levels were detected in the MC-LR-treated TM4 cells, and quercetin attenuated these effects. Interestingly, quercetin suppressed MC-LR-induced phosphorylation of AKT. It effectively inhibited the accumulation of ROS in cells stimulated by MC-LR. In addition, ROS inhibitors blocked the tight junction damage that is dependent on the AKT signaling pathway induced by MC-LR. In conclusion, our results suggest that alleviates MC-LR-impaired tight junction by suppressing the ROS-regulated activation of the AKT pathway.